Chemical control of bean rust - Zambolim, Laércio; Rodrigues, Carlos Henrique; Martins, Maria Cristina del P. (Pesquisa Agropecuaria Brasileira, 2014)
Under greenhouse conditions the fungicides in ppm of the a.i., clorothalonil (1,125), mancozeb (1,200), bitertanol (125), methyl thiophanate plus thiram (400), triadimefon (125), triforine (100) and oxicarboxin (375) proved to be good protective fungicides sprayed till fifteen days before inoculation of uredospores of Uromyces phaseoli var. typica. Oxicarboxin and triforine showed curative effect when sprayed till six days, and bitertanol and triadimefon till three days after inoculation. Under field conditions the best results were obtained with oxicarboxin (0.5 kg/ha), bitertanol (0.5 kg/ha) and triforine (0.5 l/ha).